Are we tackle ready? Cross-sectional video analysis of match tackle characteristics in elite women's Rugby Union - Wilson, Fiona; Simms, Ciaran; Connors, Will (My University, 2024)
The tackle contest is the most common and most injurious match contact event in rugby and is an indicator of performance. Tackle Ready is World Rugby's tackle technique education program. Limited research has characterized the tackle contest in women's rugby. The purpose of this study is to: (1) identify the match situational characteristics, ball‐carrier and tackler technical actions demonstrated in elite women's Rugby Union and (2) to determine the extent to which Tackle Ready recommended tackle techniques were exhibited. Technical characteristics for 1500 tackle events in the 2022–2023 Women's Six Nations Championship were visually assessed according to a predefined coding framework and the Tackle Ready program. Tackles lacked full completion (0.2%) of the 22 coded Tackle Ready techniques with 47% of the recommended techniques demonstrated in each tackle on average (range 15%–98%). A high proportion of tackles involved two defenders (48%), approaching ball‐carriers from the side (38%) or oblique angles (39%), in an upright position (30%), and with initial contact made with the arm (51%). Incorrect precontact head positioning and head placement upon contact accounted for 50% and 15% of tackles, respectively, and there was a mean of 14 (95% CI 11–18) head and neck contacts to a tackler and 18 (95% CI 14–22) head and neck contacts to a ball‐carrier per game. Targeted interventions to encourage adoption of recommended techniques are needed to reduce tackle‐related injury risk in women's rugby. This study provides valuable context for future discussion across law enforcement, coach education and gender‐specific tackle coaching in the women's game.
PUBLISHED
Keywords: ball‐carry, rugby union, tackle, video analysis, women